Fly ash-based geopolymer concrete - Rangan, B. Vijaya (2008)
The Report presents a comprehensive summary of the extensive studies conducted on fly ash-based geopolymer concrete. Test data are used to identify the effects of salient factors that influence the properties of the geopolymer concrete in the fresh and hardened states. These results are utilized to propose a simple method for the design of geopolymer concrete mixtures. Test data of various short-term and long-term properties of the geopolymer concrete are then presented. The last part of the Report describes the results of the tests conducted on large-scale reinforced geopolymer concretemembers and illustrates the application of the geopolymer concrete in the construction industry. The economic merits of the geopolymer concrete are also mentioned.